Experiences of teachers in managing dual roles: As a school head and class adviser - Jangelynne A. Torrino; Genesis B. Naparan (Eureka: Journal of Educational Research, 2024)
The purpose of this study was to describe the experiences of teachers in managing dual roles – as an administrator and class adviser. This study utilized a qualitative research method, particularly a case study design using Merriam's Approach. Twelve participants were teachers from the Zamboanga Sibugay division, designated as school heads and class advisers in their schools. Interviews were done to gather information and analyze their responses using Merriam by developing one theme to answer the objectives. The findings result in three themes: descriptions of school heads to their performance, struggles of school heads in performing dual roles, and coping strategies employed by the school heads to perform their dual roles. They found their dual role fulfilling and challenging and managed their struggles by applying different coping strategies. The efforts they rendered toward their dual roles were remarkable and their dual roles performance was recognized and appreciated. Thus, teachers in rural areas who served also as school administrators need to manage their time in doing their huge responsibilities.